2020
DOI: 10.1051/0004-6361/201937048
|View full text |Cite
|
Sign up to set email alerts
|

Importance of radiative effects in gap opening by planets in protoplanetary disks

Abstract: Recent ALMA observations revealed concentric annular structures in several young class-II objects. In an attempt to produce the rings and gaps in some of these systems, they have been modeled numerically with a single embedded planet assuming a locally isothermal equation of state. This is often justified by observations targeting the irradiation-dominated outer regions of disks (approximately 100 au). We test this assumption by conducting hydrodynamics simulations of embedded planets in thin locally isotherma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 35 publications
3
30
0
Order By: Relevance
“…6 reveals azimuthal asymmetries in the temperature variations from which we calculated the maximum temperature contrast reached in the planetary spiral wake with A219, page 9 of 17 respect to the disk background as 17%. The obtained value is in a good agreement with Ziampras et al (2020; their contrast from 2D simulations was 15%). Figure 7 then shows that in our radiative simulation, the spiral arms have a decreased density contrast (again as in Ziampras et al 2020) and their winding is less tight in the outer disk.…”
Section: Outer Gap Edge Instabilitysupporting
confidence: 85%
See 1 more Smart Citation
“…6 reveals azimuthal asymmetries in the temperature variations from which we calculated the maximum temperature contrast reached in the planetary spiral wake with A219, page 9 of 17 respect to the disk background as 17%. The obtained value is in a good agreement with Ziampras et al (2020; their contrast from 2D simulations was 15%). Figure 7 then shows that in our radiative simulation, the spiral arms have a decreased density contrast (again as in Ziampras et al 2020) and their winding is less tight in the outer disk.…”
Section: Outer Gap Edge Instabilitysupporting
confidence: 85%
“…The obtained value is in a good agreement with Ziampras et al (2020; their contrast from 2D simulations was 15%). Figure 7 then shows that in our radiative simulation, the spiral arms have a decreased density contrast (again as in Ziampras et al 2020) and their winding is less tight in the outer disk. The latter can be explained by the dependence of the pitch angle tan β h/|1 − (r/r p ) 3/2 | (Zhu et al 2015), which grows as h becomes puffed up in the outer disk in the presence of gap irradiation.…”
Section: Outer Gap Edge Instabilitysupporting
confidence: 85%
“…Recent numerical simulations of planet-disk interaction have shown that the propagation and dissipation of planet-driven spiral waves and the number and depth of associated gaps strongly depend on the thermal properties of the disk gas, in particular, the cooling timescale of the disk gas (Miranda & Rafikov 2020;Zhang & Zhu 2020;Weber et al 2019;Ziampras et al 2020). Inspired by these studies, we run three hydrodynamical simulations: (1) a locally isothermal simulation, adopting an isothermal equation of state (hereafter isothermal model); (2) an adiabatic simulation, adopting an adiabatic equation of state with an adiabatic index γ = 1.4 and β = 1 (hereafter β = 1 model), where β is defined as the multiplication of the cooling time t cool and local orbital frequency Ω, β ≡ t cool Ω; and (3) an adiabatic simulation with γ = 1.4 and β = 100 (hereafter β = 100 model).…”
Section: Hydrodynamical Simulationsmentioning
confidence: 99%
“…One of the first images to come from ALMA was the now famous HL Tau disc, a disc surrounding a young, nearby star in the Taurus star-forming region [67]. Further observational studies, in particular, the Disc Substructures at High Angular Resolution Project (DSHARP) [68], have shown that discs around young stars display features than can be attributed to a change in disc composition [69][70][71][72] as a function of radius, or the presence of fledgling planets within those discs [73][74][75][76][77] (although the latter scenario is still hotly debated [78,79]).…”
Section: Destruction Of Protoplanetary Discsmentioning
confidence: 99%